2005
DOI: 10.1002/cbdv.200590036
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of New Territrem B Analogues

Abstract: Some 23 analogues of the potent acetylcholinesterase (AChE) inhibitor territrem B (1) were designed, synthesized, and tested for their biological activities. Some of the new synthetic derivatives exhibited IC50 values for AChE inhibition in the upper micromolar range. Molecular-modeling studies indicated that a planar conformation seems to be crucial for AChE inhibition. The two N-atoms of the piperazine moieties in 5o, 5p, and 5r might further enhance the inhibitory effects. The cytotoxicities of selected com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Despite difficulties in the synthesis of TB, there are reported SAR studies involving TB, its naturally occurring close analogues, and their synthetic derivatives. Important contributions of the A-ring enone, D-ring pyran-2-one, and aromatic E-ring in binding have been noted, and these observations are consistent with the various protein–ligand interactions seen in the structure. Docking studies involving TB have not been successful in predicting the correct mode of binding .…”
supporting
confidence: 56%
“…Despite difficulties in the synthesis of TB, there are reported SAR studies involving TB, its naturally occurring close analogues, and their synthetic derivatives. Important contributions of the A-ring enone, D-ring pyran-2-one, and aromatic E-ring in binding have been noted, and these observations are consistent with the various protein–ligand interactions seen in the structure. Docking studies involving TB have not been successful in predicting the correct mode of binding .…”
supporting
confidence: 56%
“…The substantial and innovatory activity of territrem B encouraged the search for new territrem B derivatives. Preliminary structure–activity investigations suggested that the 2‐en‐1‐one moiety and the planar conformation were essential for the AChE inhibitory activity . No BuChE inhibition has been observed with territrem B …”
Section: Othersmentioning
confidence: 99%
“…A definitive hypothesis on the development of AD, which may unify the enormous number of neuropathological and neurochemical findings, has not been established. Although acetylcholine degradation was evidenced to be related to AD syndrome, wherein AChE inhibition continues to be an efficient therapeutic modality for AD treatment, 3,4 increasing studies suggest that excessive reactive oxygen species (ROS) produces oxidative stress and has been implicated in the pathogenesis of neurodegenerative diseases including AD and PD. [5][6][7] Clonal pheochromocytoma PC12 cells provide a convenient and well-studied model system for investigation of neuronal injury in vitro.…”
Section: Introductionmentioning
confidence: 99%